The Influence of Verb-Based Implicit Causality Information and Second Language Proficiency on Chinese English Learners’ Pronoun Anaphoric Inference: Evidence from Eye Movements - Huan Liu; Shifa Chen; Ruiyong Liu; Huinan Du (Behavioral Sciences)
Implicit causality (IC) is a phenomenon where verbs supply information about the potential cause of the behavior or state to one of the antecedents (e.g., “Mary praised David because…” will continue about David, not Mary). The study examines the influence of IC information and second language (L2) proficiency on Chinese English learners’ pronoun anaphoric inference. Results from an eye-tracking study showed that Chinese English learners can actively use IC information in making pronoun anaphoric inference. Additionally, compared to low-proficiency learners, high-proficiency learners spent less time on making pronoun anaphoric inference. The findings indicate that Chinese English learners can activate IC information early, before the disambiguating information appears, thus supporting the focusing account. Furthermore, L2 proficiency also affects this process.